MICROENCAPSULATION OF ASTAXANTHINUSING IONOTROPIC GELATION METHOD ISOLATED FROM THREE CRAB VARIETIES - V., Suganya; Asheeba, S. T. (International Journal of Current Pharmaceutical Research, 2015)
Objective: The objective of the present study was to prepare microencapsulated astaxanthin isolated from three crab varieties. Methods: Astaxanthin was isolated from Portunus sanguinolentus (Three Spotted Crab), Callinectes sapidus (Blue Crab), and Paralithodes brevipes (Spiny King Crab) using hexane: isopropanol and microencapsulated astaxanthin were prepared by 2% sodium alginate and 3% calcium chloride using ionotropic gelation method. The prepared microsphere was evaluated for SEM analysis, drug content, and encapsulation efficiency and swelling studies. Results: The microspheres obtained were heterogeneous in size, round shaped with smooth surface and with no obvious dents. The practical drug content varied between 35.25 mg to 42.21 mg. The encapsulation efficiency was found to be higher in blue crab (90.42 %) when compared with other crab varieties along with astaxanthin standard. The result showed that the swelling ratio at pH 1.2 was lesser than at pH 7.4. Conclusion: Thus the result gained revealed that the microencapsulated astaxanthin could support the concept of sustained release in drug therapy.